Solution: Alyssa is incorrect.
In fact
.
If we cross-multiply the above equation, we have:
![6 \times 12 = 9 \times 8](https://tex.z-dn.net/?f=6%20%5Ctimes%2012%20%3D%209%20%5Ctimes%208)
![72 = 72](https://tex.z-dn.net/?f=72%20%3D%2072)
Therefore, they are equal.
Also, if we reduce the given fractions, we have:
![\frac{6}{8} =\frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B8%7D%20%3D%5Cfrac%7B3%7D%7B4%7D)
And
![\frac{9}{12}=\frac{3}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B12%7D%3D%5Cfrac%7B3%7D%7B4%7D)
Since both the fractions reduced to
, therefore fractions are equivalent.
The <em>first three</em> elements of the <em>recursive</em> series are 6, 10, 8. (Correct choice: B)
<h3>How to generate values from a recursive function</h3>
In this question we have a kind of <em>recursive</em> function known as Fibonacci's function, where a value of the series is generated from at least <em>immediately previous</em> elements. In this case, we need to find the <em>first</em> three elements from the <em>fifth</em> and <em>fourth</em> elements of the series:
![a_{n-2} = a_{n-1} - a_{n} + 4](https://tex.z-dn.net/?f=a_%7Bn-2%7D%20%3D%20a_%7Bn-1%7D%20-%20a_%7Bn%7D%20%2B%204)
a₄ = a₅ - a₆ + 4
a₄ = - 2 - 0 + 4
a₄ = 2
a₃ = a₄ - a₅ + 4
a₃ = 2 - (- 2) + 4
a₃ = 8
a₂ = a₃ - a₄ + 4
a₂ = 8 - 2 + 4
a₂ = 10
a₁ = a₂ - a₃ + 4
a₁ = 10 - 8 + 4
a₁ = 6
The <em>first three</em> elements of the <em>recursive</em> series are 6, 10, 8. (Correct choice: B)
To learn more on recursive series: brainly.com/question/8972906
#SPJ1
Answer:
y=3x-1
Step-by-step explanation:
Answer:
He would have to do 13 rides.
Step-by-step explanation:
If he initially pays $7, which lets him pay only $1 for each ride, so when he spends $20, he would have done 13 rides.
2x-7/2 = 3-6-5x/6
⇒ 2x+ 5x/6= -3+ 7/2
⇒ 2 5/6x= 1/2
⇒ x= (1/2)/ (2 5/6)
⇒ x= 3/17
The final answer is x= 3/17~